Effect of heat waves and fine particulate matter on preterm births in Korea from 2010 to 2016. (February 2021) - Kwag, Youngrin; Kim, Min-ho; Oh, Jongmin; Shah, Surabhi; Ye, Shinhee; Ha, Eun-Hee
Abstract: Background: Previous studies have reported that fine particulate matter (PM2.5 ) affects the incidence of premature births. In addition, recent studies have suggested that heat waves have a negative impact on birth outcomes. However, the combined effect of PM2.5 and heat waves on the incidence of premature birth is controversial. This study investigated the independent and combined effects of PM2.5 and heat wave exposures during the 1st and 2nd trimesters on premature birth. Methods: The National Statistical Office of Korea provided birth data from 2010 to 2016. Preterm birth was defined as birth between 22 and 36 weeks. To assess the exposure to PM2.5 and heat waves, we used PM2.5 data estimated by the Community Multiscale Air Quality Modeling System (CMAQ) and heat wave warning data provided by the Korea Meteorological Administration. A multivariate logistic regression was used to investigate the risk of preterm birth according to the exposure to PM2.5 and heat waves during the 1st and 2nd trimesters, and it was adjusted for residential area, year of birth, season of birth, parity, education level of the mother, age of the mother, and sex of the baby. Results: In the 2nd trimester, compared with the 0 h of heat wave exposure (≤67 percentile), 62.50–314.00 h (79–88 percentile) and>315.00 h of heat wave exposure (>88 percentile) were both significantly associated with preterm birth (OR for 79–88 percentile, 1.037, 95% CI, 1.003–1.073; OR for > 88 percentile, 1.174, 95% CI, 1.134–1.215). However, PM2.5 exposure was not significantly associated with preterm birth. On the other hand, in the analysis to evaluate the combined effect of PM2.5 and heat wave exposures of the 2nd trimester, compared with 0 h of heat wave exposure (≤67 percentile) and<11.64 μg/m 3 (≤25 percentile) of PM2.5, 11.64–22.74 μg/m 3 (≤25 percentile), 22.74–27.58 μg/m 3 (26–50 percentile), and 27.57–32.39 μg/m 3 (51–75 percentile) of PM2.5 exposure combined with>315.00 h of heat wave exposure (>88 percentile) were all significantly associated with preterm birth. In addition, the effect size was increased with an increase of PM2.5 exposure (OR for ≤ 25 percentile, 1.148, 95% CI, 1.095–1.203; OR for 26–50 percentile, 1.248, 95% CI, 1.178–1.323; OR for 51–75 percentile, 1.370, 95% CI, 1.245–1.507). Conclusion: Our findings suggest that the combined effect of heat wave and PM2.5 exposure during the 2nd trimester on the risk of preterm birth was greater than that of each exposure alone. In other words, exposure to PM2.5 increases the impact of heat waves on the risk of preterm birth. These results indicate that control of prenatal exposure to fine particular matter and extreme temperatures is important for the prevention of preterm birth.